Flash & crash days : Brazilian theater in the postdictatorship period - George, David Sanderson (New York : Garland Pub., 2000)
"Flash and Crash Days: Brazilian Theater in the Post-Dictatorship Period examines how the absence of censorship and the exigencies of protest and ideological purity have given rise to a variety of theatrical modes. These new modes, which Brazil has never experienced in the past, allow all voices the opportunity to be heard in the marketplace of artistic ideas: women's perspectives, sexual identity, psychological issues, the individual in society, and religion.
Flash and Crash Days is a volume that reflects upon the theater produced in Brazil during the 1980s and 1990s."--Jacket.
Ch. 1. Gerald Thomas and the Postmodernist Theater in Brazil -- Ch. 2. Women Writers and the Quest for Identity: From Fiction into Playwriting -- Ch. 3. General Considerations on Scholarship, Playwriting, and Theater Companies.
Includes bibliographical references (pages 161-168) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Theater -- Brazil -- History -- 20th century; Brazilian drama -- 20th century -- History and criticism; Women dramatists, Brazilian -- 20th century -- Biography; Brazil; Brasilien; 1900 - 1999; Electronic books